Hubungan Hasil Belajar Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Teknik Mesin Universitas Negeri Padang - Junil Adri; Ambiyar Ambiyar; Fina Arfianti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Student learning outcomes were found to have several problems, both in mandatory and elective courses. Students should be able to maximize their learning outcomes because they can determine whether they pass the courses they take. This research is motivated by the problem of not maximizing entrepreneurial learning outcomes for mechanical engineering students' entrepreneurial interest in 2023 and 2024. The aim of this research is to reveal the relationship between entrepreneurial learning outcomes and entrepreneurial interest. This type of research is correlational descriptive research. The population of this study was 79 people, and the sample was 56 students. The sampling technique was carried out randomly (Simple Random Sampling). Data regarding student learning outcomes was obtained from the administration of the Department of Mechanical Engineering, FT UNP, while data on entrepreneurship learning outcomes were collected through questionnaires distributed to students using a Likert scale which had been tested for validity and reliability. The results of data analysis show that students' interest in entrepreneurship provides a significant relationship of 12.25% to entrepreneurship learning outcomes. So it can be concluded that students' interest in entrepreneurship influences entrepreneurial learning outcomes, the higher the entrepreneurial learning outcomes, the higher the interest in entrepreneurship.